REACHING THE GRASSROOTS: CONTRIBUTION OF INDIA IN AFGHANISTAN - Dutta, Mondira (European Scientific Journal, ESJ, 2014)
Women continue to live in a state of abject poverty facing the worst forms of violence in Afghanistan. One often encounters incidents like stoning to death, punishment for adultery, selling daughter/wife for opium and other such atrocities. A society fraught with illiteracy, poverty, lack of awareness, customary laws &traditions, strict religious regulations, etc, are the main causes behind such violence.India is among the top five countries who are working towards the reconstruction process in Afghanistan. Being one of the primary donors, India‘s expenditure till date has been to the tune of USD 2 billion plus. The present paper attempts to highlight the impact of government of India‘s initiatives implemented at the micro level by the NGO partner ‗Hand in Hand Afghanistan Organization‘ (HIHAO) targeting the women and community members in Afghanistan.